A Framework for Socio-scientific Issue based Pedagogy - AKALAMKAM, KALYANI; SHARMA, SMRITI (JOURNAL OF INDIAN EDUCATION, 2025)
Socio-scientific Issues (SSI) based pedagogy has been internationally recognised as one of the most effective pedagogical strategies to ensure meaningful engagement of learners in science education discourse so as to promote scientific literacy. SSIs are real life contextual scientific issues which are often open-ended, and can be controversial involving multiple viewpoints stemming from the social, political, economic, ethical and environmental perspectives. SSI not only promotes scientific literacy but also critical thinking, socio-scientific reasoning as well as other 21st century skills in learners across all grades and stages. However, SSI based approach is not easy as the teacher needs to be aware of the complexity of issues and should also have the ability to bring in the multiple perspectives so as to enable the learners to comprehend and appreciate various dimensions. In this backdrop, the present paper discusses the importance and possibilities of positioning SSI in pre-service science teacher preparation. Insights developed from a designbased intervention in pre-service teacher education are discussed. In order to promote preservice science teacher’s socio-scientific reasoning, an SSI based module was designed and implemented. Delving into the analysis of this pedagogical approach of engaging pre-service teachers in SSI, a framework for SSI based pedagogy in science classroom at all levels is proposed. Four aspects of this framework designed by the authors—SSI unit, teacher, learner and the learning environment are elaborated.